Study on Significance of Receptor Targeting in Killing of Intracellular Bacteria with Membrane‐Impermeable Antibiotics. Issue 12 (24th September 2021) - Catania, Rosa; Mastrotto, Francesca; Moore, Chris J.; Bosquillon, Cynthia; Falcone, Franco H.; Huett, Alan; Mantovani, Giuseppe; Stolnik, Snow
Abstract: Water‐soluble antibiotics are largely excluded from therapy of intracellular infections, such as Shigella spp., Listeria spp., or Salmonella spp., due to their inability to permeate mammalian cell membrane. Here, the authors study if targeting offers an advantage to deliver killing doses of membrane‐impermeable antibiotics intracellularly to infected cells. Mannose‐decorated liposomes, loaded with gentamicin, are fabricated to target mannose receptor, a recognition system of (infected) macrophages. Designing a family of liposomes with varying surface presentation of mannose ligand, the authors show a clear dependence of cellular internalization on the ligand surface presentation. Significantly for the killing of intracellular bacteria, the study demonstrates internalization of mannosylated liposomes by the entire population of macrophages, both Salmonella ‐infected and non‐infected, resulting in an efficient treatment of intracellular infection. This contrasts with non‐targeted liposomes, where internalization does not occur by a substantial subpopulation of infected cells. The study points to the significance of targeted delivery of antibiotics for treatment of intracellular infections. Abstract : Delivery of killing doses of antibiotics intracellularly is crucial to eradicate intracellular infections. Here, mannose‐oligomers targeted liposomes are shown capable of achieving this goal, in contrast to non‐targeted counterpart where the delivery does not occur to a substantial population of infected cells. Significance of targeted delivery is demonstrated by an efficient treatment of intracellular infection a model, Salmonella ‐infected macrophages.